STRUCTURAL VARIATION OF THE MEIOFAUNA COMMUNITY FROM GUADALUPE BEACH (PERNAMBUCO - BRAZIL) - Guilherme, Betânia Cristina; Alves, Priscila Da Silva; Cavalcanti, Mariana da Fonseca (Revista Nordestina de Zoologia, 2016)
The meiofauna community plays an important role in the energy flow of benthic systems, and its horizontal and vertical distribution depends on the granulometry, organic matter and physic-chemical factores (salinity, temperature, O2). In this sense, we aimed to analyze the structure and space-time variation of the meiofauna community on the Pontal de Guadalupe beach. For the biosedimentological analysis, samples were collected in the dry (October/2013) and rainy (May/2013) periods during the low tide. In each period, four (4) equidistant transects were established perpendicular to the beach line in 100 meters (02 in the upper mesolittoral and 02 in the lower mesolittoral). The mean of the meiofauna density indicated were in agreement with the literature for sandy beaches from the south coast of Pernambuco, and the meiofauna taxonomic composition was also in accordance with the results from other sandy beaches studies. In particular, to those from the south coast of Pernambuco, it presents the same qualitative-quantitative pattern. The high Nematoda abundances found in the meiofauna samples were expected, since the relevant literature describes that the global pattern of relative abundance of the large meiofauna groups in the tropics points to nematodes as the most representative. Regarding the spatial distribution in the two studied periods, we recorded the highest abundance, density and richness of the meiofauna organisms at the upper mesolittoral area. Regarding the temporal distribution, the highest densities recorded was in the rainy season, which can be due to the increase of rainfall caused by sedimentary deposition processes. The ecological studies of meiofauna are of extreme importance for the understanding of the natural processes of a sandy beach. In addition, the evaluation of the ecological role and the environmental and temporal changes of meiofauna communities can be applied in environmental monitoring programs, since this group is considered an important bioindicator of environmental impacts.